Transformasi Administrasi Perpajakan Melalui Teknologi Informasi Pasca Penerapan Aturan Baru di Wilayah Wajib Pajak Kota Semarang - Devy Kusumaningrum; Karjono; Evyana Diah Kusumawati (Politeknik bumi Akpelni, 2025)
The transformation of tax administration through the adoption of new regulations and digital technologies represents a strategic step toward strengthening the national taxation system. This study explores how the implementation of new policies affects efficiency, transparency, and compliance within tax administration, while also examining the challenges and opportunities that arise in the process. The digitalization of procedures—such as electronic tax filing and payment—has improved data accuracy and enhanced accessibility for taxpayers. Core technologies, including the Tax Management Information System (SIMP), e-Filing, e-Payment, data analytics, and artificial intelligence, are increasingly recognized for their ability to accelerate service delivery and effectively detect potential tax fraud. However, this transformation still faces significant hurdles, including infrastructure limitations, a shortage of skilled human resources, low levels of digital literacy, concerns over data security, and high system integration costs. This research aims to: (1) assess the impact of new regulatory frameworks on tax administration reform; (2) identify the most effective digital technologies supporting this transformation; and (3) uncover the main challenges and opportunities associated with the tax administration transformation process in Indonesia. Using a qualitative approach, data were collected through in-depth interviews with taxpayers across several districts in Semarang City. The study recommends increased investment in infrastructure, enhanced human resource capacity, stronger cross-sector collaboration, and the implementation of comprehensive data security policies. With careful planning and a collaborative, cross-sectoral approach, digital tax administration reform can lay the foundation for a more adaptive, transparent, and accountable tax system in the digital age.